More-than-human religions: The role of faith-based beliefs and institutions in the debate on the environment and the development agenda (Ágora Journal, 2026)
The article explores the intersection between religions, development, and environmental issues, drawing attention to the contribution of religious leaders from various traditions in promoting global ecological awareness. In addition to hegemonic faith-based beliefs and institutions such as Christianity, the text presents examples of other religious traditions that emphasize human responsibility for environmental degradation. Our focus was to address the perspectives of indigenous and Afro-Brazilian peoples, whose worldviews offer an intrinsic and harmonious relationship with nature, but still remain invisible. Based on a review of the literature and concepts such as inter-religiousness, interculturality, and “more-than-human religions,” we seek to discuss how faith-inspired beliefs and institutions can collaborate on systemic alternatives in the fight against climate change and the pursuit of development. We highlight the participation of some religious leaders in the Conferences of the Parties (COPs), which have been the main multilateral platform for addressing issues related to climate change.
Keywords: Pueblos tradicionales, desarrollo sostenible, fe e interreligiosidad.